Retroperitoneum parasitic leiomyoma: Dilemmatic diagnostic - Setyo Teguh Waluyo; Hariadi Yuseran; Ferry Armanza; Yuvens Richardo Wibowo (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. Parasitic leimyoma was found in a 38 year-old woman with complaint of mass in lower abdomen and already done biopsy by laparotomy 4 months before.2. During operation, the tumor was detached from the uterus, located retroperitoneally as high as L4 – S1 vertebrae.3. The tumor had been confirmed intraoperatively and proven histopathologically as parasitic leimyoma.4. Retroperitoneal parasitic leiomyoma is of a rare type and it needs multidisciplinary examination and approaches to increase the quality of its management.ABSTRACTObjectives: To describe a retroperitoneum parasitic leiomyoma case: a dilemma in diagnosis and operation finding.Case Report: A 38 year-old woman with 3 children visited Ulin Hospital, Banjarmasin, Indonesia, with complaint of mass in lower abdomen and about 4 months before, she underwent biopsy by laparotomy which revealed leiomyoma. Parasitic leiomyoma is a rare type of leiomyoma with predilection area in broad ligament, pelvic peritoneum, pouch of douglas, and omentum. During operation, the tumor was detached from the uterus and located retroperitoneally as high as L4–S1. It had been confirmed intraoperatively and proven histopathologically as a leiomyoma.Conclusion: Retroperitoneal parasitic leiomyoma may cause a dilemma in the diagnosis. Multidiscipline examination and approaches may increase the quality of management.